Fatty acid compositions of selected varieties of Spanish dry ham related to their nutritional implications - Fernández, Manuela; Ordóñez, Juan Antonio; Cambero, Isabel; Santos, Carlos; Pin, Carmen; Hoz, Lorenzo De La (Food Chemistry, 2007)
Five varieties of Spanish dry cured ham were studied to assess their nutritional value in relation to fatty acids. Ten hams of the Traditional Speciality Guaranteed (TSG) ‘‘Jamo´n Serrano’’, and the Protected Designations of Origin (PDO) ‘‘Jamo´n de Teruel’’, ‘‘Dehesa de Extremadura’’, ‘‘Jamo´n de Huelva’’ and ‘‘Guijuelo’’, were analysed. Iberian hams (‘‘Dehesa de Extremadura’’, ‘‘Jamo´n de Huelva’’ and ‘‘Guijuelo’’) were characterised by a lower proportion of saturated fatty acids (SFA) and a signiﬁcantly higher percentage of monounsaturated fatty acids (MUFA) than white hams (‘‘Jamo´n Serrano’’ and ‘‘Jamo´n de Teruel’’). The Iberian varieties also showed a high proportion (approximately 50%) of C18:1 n 9, while ‘‘Jamo´n Serrano’’ showed the highest percentage of C18:2n6. The PUFA/SFA (P/S) ratio of the ﬁve varieties was P 0.19, with the highest ratio corresponding to ‘‘Jamo´n Serrano’’ (0.3). The n6/n3 ratio was in the order of 13/1 in ‘‘Jamo´n Serrano’’ and ‘‘Jamo´n de Huelva’’, and ranged from 9.3/1 to 10.3/1 in the other varieties. The most favourable hypocholesterolemic/Hypercholesterolemic (h/H) ratio (P2.5) was found in the Iberian varieties. TSG ‘‘Serrano’’ was shown to supply the lowest percentage of the recommended daily intake of MUFA, the Iberian varieties showed the highest percentage of the daily intake of long-chain PUFA, and PDO ‘‘Dehesa de Extremadura’’ showed the highest percentage of the intake of C18:3n3. The higher MUFA proportion and h/H ratio observed in the Iberian hams, together with their contribution to the recommended daily intake of fatty acids, would make these products more suitable for healthier diets, although consumption must be recommended in moderation.
Keywords: fatty acids; hypercholesterolemic; hypocholesterolemic; n à 3; n à 6; n-3; n-6; spanish dry cured ham

Fatty acid compositions of selected varieties of Spanish dry ham related to their nutritional implications (Food Chemistry, 2007)
Five varieties of Spanish dry cured ham were studied to assess their nutritional value in relation to fatty acids. Ten hams of the Traditional Speciality Guaranteed (TSG) ‘‘Jamo´n Serrano’’, and the Protected Designations of Origin (PDO) ‘‘Jamo´n de Teruel’’, ‘‘Dehesa de Extremadura’’, ‘‘Jamo´n de Huelva’’ and ‘‘Guijuelo’’, were analysed. Iberian hams (‘‘Dehesa de Extremadura’’, ‘‘Jamo´n de Huelva’’ and ‘‘Guijuelo’’) were characterised by a lower proportion of saturated fatty acids (SFA) and a signiﬁcantly higher percentage of monounsaturated fatty acids (MUFA) than white hams (‘‘Jamo´n Serrano’’ and ‘‘Jamo´n de Teruel’’). The Iberian varieties also showed a high proportion (approximately 50%) of C18:1 n 9, while ‘‘Jamo´n Serrano’’ showed the highest percentage of C18:2n6. The PUFA/SFA (P/S) ratio of the ﬁve varieties was P 0.19, with the highest ratio corresponding to ‘‘Jamo´n Serrano’’ (0.3). The n6/n3 ratio was in the order of 13/1 in ‘‘Jamo´n Serrano’’ and ‘‘Jamo´n de Huelva’’, and ranged from 9.3/1 to 10.3/1 in the other varieties. The most favourable hypocholesterolemic/Hypercholesterolemic (h/H) ratio (P2.5) was found in the Iberian varieties. TSG ‘‘Serrano’’ was shown to supply the lowest percentage of the recommended daily intake of MUFA, the Iberian varieties showed the highest percentage of the daily intake of long-chain PUFA, and PDO ‘‘Dehesa de Extremadura’’ showed the highest percentage of the intake of C18:3n3. The higher MUFA proportion and h/H ratio observed in the Iberian hams, together with their contribution to the recommended daily intake of fatty acids, would make these products more suitable for healthier diets, although consumption must be recommended in moderation.